Development of Digital Learning and Literacy with the Socialization of Digital Library and E-Learning in Cuwelo 1 Elementary School - Iswanto Suwarno; Muhammad Ahmad Baballe; Irfan Ahmad; Erwin L. Rimban; Mohammad Aljanabi; Nia Maharani Raharja (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
SD Cuwelo 1 is located in Candirejo sub-district, Soka hamlet, RT 03 RW 13. Soka hamlet is on Jalan Baron, east of Cuwelo Kidul hamlet and west of Gebang hamlet. The implementation of education at the school runs effectively every Monday to Saturday with several additional extracurricular activities from the school. SD Cuwelo 1 school received 30 notebooks from the local government to improve learning, especially in the digital and information technology fields. Because of this potential, the real work lecture program is related to increasing teacher and student understanding of the importance of developing educational structures and digitization of education by socializing it to schools. The socialization was carried out 1 time with a duration of 90 minutes. The first 30 minutes explained in general about digitalization, educational transformation, ebooks in general, and the digital library of the Muhammadiyah University of Yogyakarta. Then the second 30 minutes was the application of l earning management system, digital library of Yogyakarta Muhammadiyah University and e-books in general developed by the government and private sector. and the last 30 minutes of direct application by students and questions and answers related to socialization material on that day. After the socialization takes place, it is hoped that students and students will still be connected with real work college students regarding the continuation of this socialization.